Determinación de FSH - LH como prueba de ayuda diagnóstica de ovario poliquístico en mujeres mayores de 30 años del Barrio San Vicente del Río cantón Paltas-Catacocha. - Minga Medina, Tatiana Lisbeth (2014)
Polycystic Ovarian Syndrome is an ovarian dysfunction , endocrine , metabolic and primary cause of infertility , affecting 5-10% of women , the first parameters to be determined are the values of FSH and LH as elevated levels of LH ( hormone luteinizing hormone) and FSH normal or decreased (follicle stimulating hormone ) , supporting the diagnosis. In San Vicente del Rio due to poor economic conditions , the lack of knowledge and hereditary factors , among others , influence the development of Polycystic Ovarian Syndrome , it was considered important that the female population of this area will be made to know their status checks hormonal , so it was convenient to perform the quantification of LH and FSH through electrochemiluminescence method , for it was a prospective descriptive study with a cross-sectional sample of 30 women who met the inclusion criteria . The objectives were to determine the hormones FSH and LH as presumptive evidence Polycystic Ovarian help women over 30 years, in addition to knowing the age group most vulnerable to suffer from PCOS, and finally disseminate the results to the community, concluding that the 30 women were subjected to analysis on 17 % showed increased levels of LH , and found decreased levels of FSH by 10 % and 90% normal . In addition , 27% belongs to the age group of 45-47 years , followed by 20% belonging to the age group of 30-32 years, these were women of childbearing age were found making them more vulnerable to polycystic ovary yield a presumptive diagnosis of polycystic ovarian Syndrome which equates to 17% . Key words: Follicle stimulating hormone, luteinizing hormone, Polycystic Ovary Syndrome.